Depressive symptoms at postpartum are associated with those at the second trimester of pregnancy and the antioxidant activity immediately after delivery - Asuka Hirose; Masakazu Terauchi; Tamami Odai; Kiyoko Kato; Naoyuki Miyasaka (Taylor & Francis Group, 2021)
Objective This study aimed to investigate whether depressive symptoms at postpartum are associated with oxidative stress and antioxidant activity, as well as the symptoms during pregnancy. Methods This longitudinal study enrolled 84 women in their second trimester of pregnancy. Their depressive symptoms were assessed using Edinburgh postnatal depression scale (EPDS), and their oxidative stress and antioxidant activity were assessed using reactive oxygen metabolites/8-hydroxy-2'-deoxyguanosine and biological antioxidant potential (BAP) at around 26 and 36 weeks (time points 1 and 2) of gestation, and 3-6 days and 1 month (time points 3 and 4) postpartum. We evaluated the associations between EPDS at time point 4 and various parameters at the other time points. Results Multiple regression analysis revealed that EPDS at time point 1 (adjusted odds ratio: 1.06 per 0.1 point increase; 95% confidence interval [CI]: 1.03-1.11) and BAP at time point 3 (adjusted odds ratio: 0.93 per 10 μmol/L increase; 95% CI: 0.87-0.97) were independent predictors of EPDS at time point 4. Conclusion Depressive symptoms at the second trimester of pregnancy and the antioxidant activity immediately after delivery could predict postpartum depression. TRIAL REGISTRATION UMIN-CTR UMIN000022367